Job Search with Subjective Wage Expectations - Sascha Drahs; Luke Haywood; Amelie Schiprowski (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2018)
This paper analyzes how subjective expectations about wage opportunities influence the job search decision. We match data on subjective wage expectations with administrative employment records. The data reveal that unemployed individuals over-estimate their future net re-employment wage by 10% on average. In particular, the average individual does not anticipate that wage offers decline in value with their elapsed time out of em- ployment. How does this optimism affect job finding? We analyze this question using a structural job search framework in which subjective expectations about future wage offers are not constrained to be consistent with reality. Results show that wage optimism has highly dynamic effects: upon unemployment entry, optimism decreases job finding by about 8%. This effect weakens over the unemployment spell and eventually switches sign after about 8 months of unemployment. From then onward, optimism prevents un- employed individuals from becoming discouraged and thus increases search. On average, optimism increases the duration of unemployment by about 6.5%.
Keywords: J64; D83; 330; job search; subjective expectations; structural estimation